Exploring performances versus reality in “reality” shows. In Big Brother Mzansi double trouble 2015. - Moyo, Sandile (Midlands State University, 2017)
The research explores the performances versus reality in “reality” the reality television show Big Brother Mzansi double trouble 2015. The research sought to explore whether what is termed reality is indeed ‘real’ or is a combination of performances by the housemates. The research deploys theories of framing and realism to ascertain the extent to which the show was a depiction of ‘reality’ or simply conformed to predetermined frames constructed by Endemol, the producers of the show. The research employed archival research to collect data. The archive was constituted of episodes of the show downloaded from YouTube. The study employed qualitative methodology designed as a case study in attempt to answer the question why and what aspects of Big Brother Mzansi double trouble 2015 constitute reality and performances. In the analysis of the data semiotics and hermeneutics of interpretation were used. The study found out that what we term “reality” is not in actual fact real as there are many factors such as house rules and cinematographic decisions that distort reality hence at the end of the day describing the show as reality becomes a misnomer. In such a scenario the researcher found out that realities have never been real.